Classroom Management Problems Faced by English Education Students at Faculty of Teacher Training and Education University of Mataram Undertaking the Campus Teaching Program - Insani, Firda Aprilia; Sujana, I Made; Farmasari, Santi; Wilian, Sudirman (Program Studi Pendidikan Bahasa Inggris, 2024)
This study addresses the challenges English Education students face in developing relationships, motivation, and engaging instruction in English classes. The research design is descriptive qualitative research, and the data collection methods include observation sheets, interviews, and document analysis. The study participants are five students who participated in the Kampus Mengajar or Campus Teaching (KM) program at University of Mataram and seek to identify the problems they encounter in classroom management, how they solve them, and how well they manage their classrooms. The result of both observation and interview founded that there are included six problems faced by KM-5 students during teaching practice i.e., (1) Naughty students, (2) Underestimate the teacher, (3) Hyper active students, (4) Passive students in learning activities, (5) Crowded classes and (6) Bored students. The efforts given by the KM students in dealing with the problems are building good teacher-student relationships, making the lesson more attractive, giving a small gift to catch students' attention, giving word motivation, changing students' seat positions, and making some games related to the topic discussion. The results highlight the need for further support and development opportunities for student teachers to enhance their classroom management skills and teaching practice.